Exploring the nexus between banking stability and market value: Evidence from the Iraqi banking sector - Ali Abdulhassan Abbas; Anwar Abdul Kareem Hassouni (Economics, Management and Sustainability)
Purpose: This study aims to investigate the relationship between banking stability and market value in the Iraqi banking sector, exploring how the stability of banks impacts their market capitalization. Methodology: The study employs a quantitative approach, utilizing financial ratios such as return on assets, equity/assets, and the z-score index to quantify banking stability. Market value is measured using banks' share prices and outstanding shares. A sample of 17 Iraqi banks is analyzed over a four-year period, employing statistical analysis to examine the relationship between banking stability and market value. Results: The findings reveal a positive relationship between banking stability and market value. Banks with strong risk management practices, adequate capital buffers, and effective regulatory oversight inspire greater confidence among depositors and investors, translating into higher market valuations. Conversely, banks facing poor governance, high non-performing loans, and thin capital cushions struggle to achieve stability, eroding their market value. Theoretical Contribution: The study contributes to the existing literature by providing empirical evidence on the crucial role of banking stability in shaping market valuations. It highlights the importance of sound banking practices, regulatory frameworks, and risk management in enhancing investor confidence and, ultimately, the market value of banks. Practical Implications: The findings offer insights for policymakers, regulators, and financial institutions in Iraq and other regions. Promoting banking stability through enhanced prudential oversight, governance practices, risk management capabilities, and financial inclusion can favorably impact the market valuation and development of the banking system.